2022
DOI: 10.3390/biology11071057
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of Innate Immune Response in Acetaminophen-Induced Liver Injury

Abstract: Acetyl-para-aminophenol (APAP), a commonly used antipyretic analgesic, is becoming increasingly toxic to the liver, resulting in a high rate of acute hepatic failure in Europe and the United States. Excessive APAP metabolism in the liver develops an APAP–protein adduct, which causes oxidative stress, mitochondrial membrane permeability, and hepatic necrosis. HMGB-1, HSP, nDNA, mtDNA, uric acid, and ATP are DMAPs released during hepatic necrosis. DMAPs attach to TLR4-expressing immune cells such KCs, macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 140 publications
0
13
0
Order By: Relevance
“…In severe circumstances, liver transplantation is the only option that might possibly save the patient’s life. APAP-induced liver injury is emerging as a public health issue ( Yang et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…In severe circumstances, liver transplantation is the only option that might possibly save the patient’s life. APAP-induced liver injury is emerging as a public health issue ( Yang et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with excessive APAP leads to severe oxidative stress and activates the innate immune system in the liver, which induces persistent inflammatory response and hepatocyte damage. 27 Therefore, after confirming that the lack of ZBTB22 aggravates the level of oxidative stress in APAP-induced MPHs, inflammation, and apoptotic levels were subsequently detected. ZBTB22 deficiency increased the translocation of NFκB-p65 from the cytoplasm to the nucleus ( Figures 3 A and 3B), as well as up-regulated the protein expression levels of NF-κB-p65 in the nuclear ( Figure S4 A).…”
Section: Resultsmentioning
confidence: 84%
“…Several lines of accumulating evidence have suggested that leukocyte recruitment is essential for the development of APAP-induced hepatotoxicity [3,32,33]. Therefore, we evaluated the influence of sivelestat on intrahepatic leukocyte recruitment after the APAP challenge.…”
Section: Treatment With Sivelestat Reduces Hepatic Neutrophil Infiltr...mentioning
confidence: 99%